Overview of Genotyping Technologies and Methods. Issue 4 (7th April 2023) - Kockum, Ingrid; Huang, Jesse; Stridh, Pernilla
Abstract: Genetics is a cornerstone of molecular biology, and there have been significant developments in genotyping technologies during the last decades. Genotyping can be used for a wide range of applications, such as genealogy, assessing risks and causes for common diseases and health conditions, animal and human research, and forensic investigations. So how do you perform a genetic study? This overview covers key concepts in genetics, the development of common genotyping methods, and a comparison of several techniques, including PCR, microarrays, and sequencing. A general process of the steps involved in genotyping, from DNA preparation to quality control, is described with relevant protocols referenced. Different types of DNA variants are illustrated, including mutations, SNP, insertions, deletions, microsatellites, and copy number variations, with examples of their involvement in disease. We discuss the utilities of genotyping, such as medical genetics, genome‐wide association studies (GWAS), and forensic science. We also provide tips for quality control, analysis, and results interpretation to help the reader design and perform a genetic study or scrutinize such studies from the literature. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.